Efektifitas hypnotherapy sebagai intervensi non farmakologis untuk mengurangi kecemasan pada ibu hamil - Lisnawati Lisnawati; Widia Shofa Ilmiah (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Anxiety during pregnancy is one of the psychological disorders experienced by pregnant women and can have a negative impact on the delivery process and fetal development. One non-pharmacological approach that can be used to reduce anxiety is hypnotherapy. Purpose: To assess the effectiveness of hypnotherapy in reducing anxiety levels in pregnant women undergoing examinations at the Plaingkau Community Health Center. Method: The research design applied was a pre-experimental one-group pretest-posttest design. A total of 20 pregnant women were selected as respondents using purposive sampling. The instrument used to measure anxiety levels in mothers was the Hamilton Anxiety Rating Scale (HARS) before and after the intervention was given. Hypnotherapy was conducted twice a week and supplemented with audio recordings for independent practice at home. Results: Bivariate analysis using the Paired t-Test showed a significant decrease in anxiety levels, with an average difference of 18.050 and a p-value of 0.000. Conclusion: Hypnotherapy is an effective non-pharmacological intervention for reducing anxiety in pregnant women and is suitable for implementation in antenatal care services at the primary health care level. Suggestion: Future research should involve a larger sample size and use a more robust experimental design, for example by including a control group to improve the validity of the comparison of results.